O doux parler - Lasso, Orlando di,Ronsard, Pierre de,Sandberger, Adolf (Breitkopf and Härtel, 1927)
O doux parler – O Vermeillons
For double chorus (SATB SATB), unaccompanied. - Full Score
Keywords: Polyphonic chansons